Liberalizmus és neoabszolutizmus. Alkotmánypolitika és igazgatási reform a Habsburg Birodalomban Alexander Bach minisztersége idején, 1848-1859 (Liberalism and neoabsolutism. Constitutional politics and administrative reform in the Hapsburg Empire during the ministry of Alexander Bach from 1848 to 1859) - Seiderer, Georg (Aetas, 2012)
This paper examines the continuities and changes during the ministry of internal affairs minister Alexander Bach, from the time of his invitation to Felix zu Schwarzenberg's government. The author is lokking for an answer to the question wether the neoabsolutist government policies of the 1850s had any liberal characteristics. The paper will not provide a detail review of Bach's internal affairs policies, but rather focus on two aspects of central importance: Bach's constitutional politics and his vision on local administrative bodies. On the basis of these, we can claim that Bach's break-up with his liberal past did not occur in 1848 or 1849: his policy sought to enact the March constitution of 1849 up until 1850, his standpoint was mainly the same as in 1848. From 1851 on, he gave up liberal politics - despite some obviously surviving elements in his theory, which were due to his conviction, crystallized in the meantime, that Austria could not be governed as a constitutional state. However, one would oversimplify to call his politics conservative. The difference between his bureaucratic etatism and the aristocratic conservatism was not a mere question of degree.